PERANCANGAN MODEL BASIS DATA PENCARIAN JASA PEKERJA RUMAH TANGGA (PRT) - Raras Triastari, (2021)
The process of finding information about domestic worker services has tended to be difficult due to the absence of information media. In addition, it is difficult for domestic workers to offer their services in the absence of promotional media that can be accessed by prospective employers. Based on this need, it is felt necessary to create a database that can connect domestic workers and prospective employers. The database to be designed uses the Database Life Cycle (DBLC) method which has the stages of designing a conceptual model, designing a logical model, and designing a physical model. With this database, it is hoped that it can assist prospective employers in finding domestic workers and can also assist domestic workers in promoting their services